Estimation of net benefit from the proposed Ban La hydropower project in Nghe An Province, Vietnam:Master of Environmental Management in Development planning Thesis - Nguyen, Thi Hoang Hoa (University Malaysia Sarawak, 2020)
This study evaluates economic and environmental impacts of Ban La project on local communities: upstream of the Ban La dam; flooded area and irrigation areas downstream from the proposed dam. Private costs and benefits as well as public costs and benefit are estimated for the project in order to arrive at the total net social benefits. Contingent Valuation Method (CVM) is used to estimate the costs and benefits associated with intangible item or non-market goods. The study found that the net present value of social benefits at 10% discount rate and 30 years project operation period is positive (BVND 533.8). Benefit-Cost ratio is 3.18 and Internal Rate of Return (IRR) is 11%. Sensitivity analysis is also performed to detect responsiveness of the investment to changes in discount rate, changes in output of the project as well as different scenarios of project lifespan.